Principled labor law : U.S. labor law through a Latin American method - Gamonal Contreras, Sergio, 1966-; Rosado Marzán, César F., 1975- (Oxford scholarship online., 2019)
Providing a Latin American perspective of the 'idea' of labour law, which the authors call 'principled labour law', this text outlines a jurisprudential method based on worker protection, i.e., the protective principle, and its derivative principles: primacy of reality, nonwaiver and continuity. It argues that principled labour law is needed given that many labour law scholars have declared a crisis in their field due to the ascendancy of 'fissured,' 'gig,' 'precarious' and 'nonstandard' work.